PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI BERBASIS WEB PADA KONSEP SISTEM PENCERNAAN DI SEKOLAH MENENGAH ATAS - Ifa Safira; Ismail Ismail; A.Mushawwir Taiyeb (UNM Journal of Biological Education, 2018)
This type of research is research and development (R & D) which aims to develop a web-based instructional media of biology using Moodle that are valid, practical and effective at the concept of the digestive system. Research and development phase refers to the ADDIE development model that consists of five phases: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Assessment instruments consists of three,  (1) the validity instrument that are instrument assessment of web-based Instructional media of biology validity and assessment instruments validity of the questionnaire, (2) a practical instrument of teachers and students' response questionnaire to web-based instructional media of Biology, and (3) the instruments effectiveness that are observational activities and student learning outcomes. Based on data analysis, the average of instructional media validity was obtained by three validators is 4.80 (very valid). Practicality of media was obtained by teacher’s responses is 4.60 (high) and the student's response is 4.51 (high). The effectiveness of media value obtained about 6 of the 7 observed activities that has met the criteria of activity and 88.88% of students achieve a mastery learning value. The improvement of Biology learning outcome based on data analysis was obtained by the normalized gain of 0.73 (high category). Based on the results of this study concluded that web-based instructional media of biology that was developed are valid, practical, and effective.